The Progress of Hard Carbon as an Anode Material in Sodium-Ion Batteries - Tan, Suchong; Yang, Han; Zhang, Zhen; Xu, Xiangyu; Xu, Yuanyuan; Zhou, Jian; Zhou, Xinchi; Pan, Zhengdao; Rao, Xingyou; Gu, Yudong; Wang, Zhoulu; Wu, Yutong; et al. (Molecules (Basel, Switzerland), 2023)
When compared to expensive lithium metal, the metal sodium resources on Earth are abundant and evenly distributed. Therefore, low-cost sodium-ion batteries are expected to replace lithium-ion batteries and become the most likely energy storage system for large-scale applications. Among the many anode materials for sodium-ion batteries, hard carbon has obvious advantages and great commercial potential. In this review, the adsorption behavior of sodium ions at the active sites on the surface of hard carbon, the process of entering the graphite lamellar, and their sequence in the discharge process are analyzed. The controversial storage mechanism of sodium ions is discussed, and four storage mechanisms for sodium ions are summarized. Not only is the storage mechanism of sodium ions (in hard carbon) analyzed in depth, but also the relationships between their morphology and structure regulation and between heteroatom doping and electrolyte optimization are further discussed, as well as the electrochemical performance of hard carbon anodes in sodium-ion batteries. It is expected that the sodium-ion batteries with hard carbon anodes will have excellent electrochemical performance, and lower costs will be required for large-scale energy storage systems.